Solid-state characteristics of pre- and post-spray dried active pharmaceutical ingredients, salts and co-crystalline forms - Paluch, Krzysztof Jan (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2011)
Salt or co-crystal formation is one of the methods of altering the physicochemical properties of an active pharmaceutical ingredient (API). The drug characteristic can also be changed upon processing. This thesis focused on solid-state characteristics of pre- and post-spray dried APIs, salts and co-crystalline forms. Two model APIs were investigated, chlorothiazide (CTZ), as an example of poorly water soluble acidic API, and salbutamol (SB), as an example of an amphoteric molecule, which is sparingly soluble in water. CTZ and SB were chosen in order to investigate how the selection of co-formers alters the physicochemical properties of the solid state form of the new forms of the APIs. Sodium and potassium cations, as the co-formers, were selected for CTZ, while the properties of SB were altered with adipate and succinate anions.
Keywords: Pharmaceutics, Ph.D.; Ph.D. Trinity College Dublin